Advances in Doppler ultrasound applications in obstetrics - Sosa Olavarría, Alberto (2015)
Doppler velocimetry is one of the most important advances in non invasive exploration of fetal condition whose information allows the maternal and fetal medicine expert in the diagnosis and conducts to preserve health of the fetus and neonate. We will briefly review advances and uses of velocimetry in perinatology.